USE OF HIGH RESOLUTION GOOGLE EARTH IMAGES FOR LAND USE/LAND COVER MAPPING IN THUY TRIEU COMMUNE, THUY NGUYEN DISTRICT, HAI PHONG CITY - Quang Bao, Tran; Quang Duong, Pham (Journal of Forestry Science and Technology, 2018)
The aim of this study was to establish land use map in 2016 using object-based classification technique in Google Earth image and analyze land use/land cover changes in the landscape of Thuy Trieu commune, Thuy Nguyen district, Hai Phong province in Vietnam over a period of 3 years (2013 - 2016). This paper introduced an object-based method to Google Earth image to map the land cover in Thuy Trieu commune in 2016, which approach applied multi-resolution segmentation algorithm of eCognition Developer and an object-based classification framework. In addition, landuse maps from 2013 created by Landsat 8 image were used to analyze the change in landuse types in 3 years period. The object-based method clearly discriminated the different land cover classes in Thuy Trieu in eight mainland use types with overall kappa value was 0.88. After overlaying landuse map of 2013 created by Landsat 8 image with the landuse map of 2016, all land cover changed during 2013 - 2016 were received. The results of this study will partly contribute to the development of tools in land management, which will save time, money and improve the accuracy of map data updates.